Association between e-cigarette smoking and insulin resistance using the triglyceride-glucose index in Korean adults: Korea National Health and Nutrition Examination Survey - Lim, Dahae; Choi, Jung In; Kwon, Ryuk Jun; Lee, Sang Yeoup; Cho, Young Hye; Park, Eun Ju; Lee, Youngin; Lee, Sae Rom; Son, Soo Min; Kim, Yun Jin; Lee, Jeong Gyu; Yi, Yu Hyeon; et al. (Korean journal of family medicine, 2025)
Background: Insulin resistance contributes to the development of cardiovascular disease and type 2 diabetes mellitus. Smoking leads to an increase in triglyceride levels, which, in turn, increases insulin resistance. Although the number of e-cigarette users has increased in recent years, few studies have investigated the association between ecigarette use and insulin resistance. Therefore, this study aimed to determine the association between e-cigarette use and insulin resistance using the triglyceride-glucose (TyG) index in Korean adults.Methods: This study included 4,404 healthy adults aged ≥20 years who participated in the Korea National Health and Nutrition Examination Survey between 2019 and 2020. Participants were categorized as never-smokers or ecigarette users, and the TyG index was categorized into low- and high-TyG index groups according to the median value (9.22). A logistic regression analysis was performed to determine the association between e-cigarette smoking and insulin resistance.Results: E-cigarette users had a higher TyG index than never smokers (e-cigarette: mean=9.35; never: mean=9.18; P<0.001). The ecigarette users had a higher risk of being in the high TyG index group than never-smokers (odds ratio [OR], 1.38; 95% confidence interval [CI], 1.03–1.84). In the subgroup analysis stratified by sex, age, and body mass index, a higher OR for a high TyG index was observed in men (OR, 1.46; 95% CI, 1.03–2.08) and individuals aged 60 years or older (OR, 3.74; 95% CI, 1.14–12.30).Conclusion: Our findings suggest that e-cigarette use is significantly associated with insulin resistance.